낙엽송 개벌 임분에서 타워야더를 이용한 전목수확시스템의 작업비용 분석 - 조민재; 조구현; 오재헌; 한한섭; 차두송 (Journal of forest and environmental science , 30(1), 2014)
The productivity and cost of clear cutting operations were examined to broaden our knowledge on the harvestingsystem in a Larix leptolepis stand of Korea. The harvesting system was divided into tree operations which were chainsaw (STIHL MS440) felling, tower yarder (Koller301-4) yarding and harvester (WOODY H50) processing. The average cycle time of felling, yarding and processing were 98 s/cycle, 245 s/cycle and 150 s/cycle. The total stump-to-pile operational productivity was 43.07 m³/hr. The highest production activity was the felling 17.93 m³/hr, followed by the productivity of processing 15.62 m³/hr and then by the productivity of yarding 9.52 m³/hr. In addition the total stump-to-pile operational cost was 24,086 won/m³. The highest cost activity was the yarding 14,557 won/m³ (60.4% of the total cost), followed by the costs of processing 8,461 won/m³ (35.2%) and then by the costs of felling 1,068 won/m³. KCI Citation Count: 5